Impact of land certification on tree growing on private plots of rural households: Evidence from Ethiopia - Alemu Mekonnen; Hosaena Ghebru; Stein Holden; Menale Kassie (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2012)
The paper examines the impact of land certification on tree growing on private plots of rural households in the Amhara and Tigray regions of Ethiopia. Household and plot level panel data from before and after land certification from stratified random samples of households were used for the analysis. The results suggest a positive impact of land certification on tree growing on private plots of rural households. Law restrictions on tree planting on land suitable for agricultural production may explain why positive but lower investments in tree growing were found on plots that had been exposed to public conservation programs. The study questions the rationale of prohibiting tree growing on degraded agricultural land where tree growing is more profitable and more sustainable than continued growing of food crops.
Keywords: K11; Q15; Q23; Q24; Q56; 330; Land certification; tenure security; incentives for tree planting; investment impact; law restrictions